Poets of the Sixties as Translators of Ossetian Poetry - E. B. Dzaparova (Научный диалог, 2020)
The results of a comparative analysis of multilingual texts - the original and the translation - of poetic works by Ossetian authors (M. Tsirikhova, A. Tsarukaev, R. Asaev, G. Dzugaev, H.-M. Dzuzzati, D. Darchieva, T. Tettsoeva) in the light of the translation interpretation by famous Russian poets of the sixties (E. Evtushenko, B. Akhmadulina, R. Kazakova, B. Okudzhava, Yu. Morits) are presented. In the course of comparative analysis, it was found that some translators resorted to adapted rethinking of the lines of a foreign language text (Yu. Morits, B. Akhmadulina). It was shown that for this purpose, in some places, translators violated the formal organization of the verse, expanded the original text by adding stanzas (R. Kazakov) or, conversely, narrowed the verse of the original (B. Okudzhava, B. Akhmadulina), but changes in the structure of the original did not affect the adequate perception of the text to recipients. The features of the implementation of the original pragmatic potential in translation are commented. It is noted that translators not only find lexical means characterized by semantic affinity with the words of the original, but also embody the aesthetic component of the literary text (R. Kazakova, Yu. Moritz) and others. It is stated that some poets deliberately resorted to rethinking the artistic reality captured by the author: in the language of translation, a new work is actually created based on the poem in the original (E. Evtushenko, B. Akhmadulina).